Mobile ecosystems in global transition: Driving factors of becoming a mobile ecosystem enabled. A comparison between the US and Japan - Marco Josef Koeder; Ema Tanaka; Kaori Misawa (International Telecommunications Society (ITS), 2012)
The experiences made with i-Mode in Japan in from 2000 - 2010 suggested that the development of so called mobile ecosystems can help to trigger continuous evolution of the mobile industry and created a sustainable platform for third generation mobile networks (3G). At the same time on a global scale the linkage between mobile platforms (mobile OS) and smartphones has become tighter and also created and drove new ecosystems and revenue models. There have been previous studies explaining the general structure of mobile ecosystem but there is room for further insights into what factors would trigger and lead mobile ecosystem evolution and how factors such as competition, regulation and profitability affects a carriers decision to become an ecosystem enabler or not. The focus of this paper is on the driving factors of the investments in ecosystems from the view point of market competition conditions and profit level by comparing the market condition of the US and Japan.
Keywords: 330; mobile ecosystem; mobile operator; 3G; LTE; competition; Japan; i-mode; smartphone; revenue models; advanced data services; mobile platforms; mobile operating system; regulation policy